A Southern Hemisphere record of global trace‐metal drawdown and orbital modulation of organic‐matter burial across the Cenomanian–Turonian boundary (Ocean Drilling Program Site 1138, Kerguelen Plateau). Issue 1 (20th October 2016) - Dickson, Alexander J.; Saker‐Clark, Matthew; Jenkyns, Hugh C.; Bottini, Cinzia; Erba, Elisabetta; Russo, Fabio; Gorbanenko, Olga; Naafs, Bernhard D. A.; Pancost, Richard D.; Robinson, Stuart A.; van den Boorn, Sander H.J.M; Idiz, Erdem
Abstract: Despite its assumed global nature, there are very few detailed stratigraphic records of the late Cenomanian to the early Turonian Oceanic Anoxic Event 2 from the Southern Hemisphere. A highly resolved record of environmental changes across the Cenomanian–Turonian boundary interval is presented from Ocean Drilling Program Site 1138 on the central Kerguelen Plateau (southern Indian Ocean). The new data lead to three key observations. Firstly, detailed biostratigraphy and chemostratigraphy indicate that the record of Oceanic Anoxic Event 2 is not complete, with a hiatus spanning the onset of the event. A decrease in glauconite and highly weathered clays after the onset of Oceanic Anoxic Event 2 marks the end of the hiatus interval, which can be explained by a relative sea‐level rise that increased sediment accommodation space on the Kerguelen Plateau margin. This change in depositional environment controlled the timing of the delayed peak in organic‐matter burial during Oceanic Anoxic Event 2 at Site 1138 compared with other Oceanic Anoxic Event 2 locations worldwide. A second key observation is the presence of cyclic fluctuations in the quantity and composition of organic matter being buried on the central Kerguelen Plateau throughout the latter stages of Oceanic Anoxic Event 2 and the early Turonian. A close correspondence between organic matter, sedimentary elemental compositions and sediments recording sea‐floor oxygenation suggests that the cycles were mainly productivity‐driven phenomena. Available age‐control points constrain the periodicity of the coupled changes in sedimentary parameters to ca 20 to 70 ka, suggesting a link between carbon burial and astronomically forced climatic variations (precession or obliquity) in the Southern Hemisphere mid‐latitudes both during, and after, Oceanic Anoxic Event 2: fluctuations that were superimposed on the impact of global‐scale processes. Finally, trace‐metal data from the black‐shale unit at Site 1138 provide the first evidence from outside of the proto‐North Atlantic region for a global drawdown of seawater trace‐metal (Mo) inventories during Oceanic Anoxic Event 2.